Ant Colony Optimization Based Software Component Retrieval - Khode, Sandeep G. (My University, 2009)
Software reuse is only effective if it is easier to locate and appropriately modify a reusable component than to write it from scratch. It is the use of existing software knowledge or artifacts, also known as software components, to build new software. There are two main problems in software reuse. First, classifying software modules in a component library is a major problem in software reuse. Second, identifying appropriate software components in a library or software component retrieval is an important task in software reuse: after all, components must be found before they can be reused.Many researchers have proposed various techniques to search and retrieve components. These methods are broadly classified into six categories viz. Information Retrieval, Descriptive, Operational Semantics, Denotational Semantics, Topological, and Structural Methods. Each of these methods has certain advantages and disadvantages.In this thesis work we proposed a technique that can help re-user to identify and retrieve software component. It is based on Ant Colony Based Optimization algorithm. This algorithm is a probabilistic approach and also robust, scalable and can be modified for our purpose. In our retrieval process, its first step matches keywords, their synonyms and their interrelationships. And then with the help of ant colony optimization, generate rule for matching the component against the re-user query.
Keywords: Software Components, Ant Colony, Retrieval